An Empirical Examination of Multinational Corporate Capital Structure - Burgman, Todd A. (Journal of International Business Studies, 1996)
This paper examines whether there are systematic differences in the traditional capital structure determinants between MNCs and DCs, and if there are additional, uniquely international factors that may help explain the capital structure choice of multinational corporations. The results suggest that specific international factors such as political risk and exchange rate risk are relevant to the multinational capital structure decision, that multinationals have higher agency costs than purely domestic firms, and that international diversification does not lower earnings volatility for multinational corporations.